Celastrol and Melatonin Modify SIRT1, SIRT6 and SIRT7 Gene Expression and Improve the Response of Human Granulosa-Lutein Cells to Oxidative Stress - Rita Martín-Ramírez; Rebeca González-Fernández; Jairo Hernández; Pablo Martín-Vasallo; Angela Palumbo; Julio Ávila (MDPI AG, 2021)
An excess of oxidative stress (OS) may affect several physiological processes fundamental to reproduction. SIRT1, SIRT6 and SIRT7 are involved in protection stress systems caused by OS, and they can be activated by antioxidants such as celastrol or melatonin. In this study, we evaluate SIRT1, SIRT6 and SIRT7 gene expression in cultured human granulosa-lutein (hGL) cells in response to OS inductors (glucose or peroxynitrite) and/or antioxidants. Our results show that celastrol and melatonin improve cell survival in the presence and absence of OS inductors. In addition, melatonin induced SIRT1, SIRT6 and SIRT7 gene expression while celastrol only induced SIRT7 gene expression. This response was not altered by the addition of OS inductors. Our previous data for cultured hGL cells showed a dual role of celastrol as a free radical scavenger and as a protective agent by regulating gene expression. This study shows a direct effect of celastrol on SIRT7 gene expression. Melatonin may protect from OS in a receptor-mediated manner rather than as a scavenger. In conclusion, our results show increased hGL cells survival with melatonin or celastrol treatment under OS conditions, probably through the regulation of nuclear sirtuins' gene expression.